Kaempferide Protects against Myocardial Ischemia/Reperfusion Injury through Activation of the PI3K/Akt/GSK-3β Pathway. (27th August 2017) - Wang, Dong; Zhang, Xinjie; Li, Defang; Hao, Wenjin; Meng, Fanqing; Wang, Bo; Han, Jichun; Zheng, Qiusheng
Abstract : The aim of this study is to investigate both the efficacy and mechanism of action of kaempferide (Kae) as a therapy for the treatment of cardiovascular disease. A rat model of myocardial ischemia/reperfusion (I/R) injury was established by ligation of the left anterior descending coronary artery for 30 min followed by a 2 h perfusion. In our study, we show that Kae remarkably improved cardiac function, alleviated myocardial injury via a decrease in myocardial enzyme levels, and attenuated myocardial infarct size in a dose-dependent manner. In addition, preconditioning treatment with Kae was found to significantly decrease serum TNF- α, IL-6, C-reactive protein (CRP), MDA, and ROS levels, while it was found to increase serum levels of SOD. Nuclear factor erythroid 2-related factor 2 (Nrf2) and cleaved caspase-3 expression levels were observed to be downregulated, while phospho-Akt (p-Akt) and phospho-glycogen synthase kinase-3 β (p-GSK-3 β ) expression levels were upregulated. However, cotreatment with LY294002 (a PI3K inhibitor) or TDZD-8 (a GSK-3 β inhibitor) was found to abolish the above cardioprotective effects observed with the Kae treatment. The data presented in this study provides evidence that Kae attenuates I/R-induced myocardial injury through inhibition of the Nrf2 and cleaved caspase-3 signaling pathways via a PI3K/Akt/GSK 3 β -dependent mechanism.